2017
DOI: 10.12669/pjms.336.13692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibrin vs cellulose based haemostatic agents with traditional haemostatic procedures in thyroid surgery

Abstract: Objective:To compare the efficacy of fibrin-based hemostat and cellulose-based hemostat with traditional procedures in patients undergoing thyroid surgery.Methods:Between January 2012 and December 2016, 255 patients were scheduled to undergo total thyroidectomy at Surgical Clinic Nis. The patients were randomized to: Group-I use of classic surgical procedures to achieve hemostasis, Group-II use Surgicel and Group-III use BeriplasResults:A statistically significant reduction of surgical time was found for Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, physical agents didn't show advantages over conventional surgical techniques on time to drain removal, length of hospital stay and seroma formation 3,4,21 . We found no studies proving physical agents being more efficient than biologically active ones 1,3,4,21 . Only Amit et al found that the use of an oxidized cellulose hemostatic agent resulted in longer time to drain removal, and consequently in length of hospital stay, if compared with conventional procedures, suggesting that postoperative hemorrhage can best be prevented by proper intraoperative hemostasis 25 .…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…However, physical agents didn't show advantages over conventional surgical techniques on time to drain removal, length of hospital stay and seroma formation 3,4,21 . We found no studies proving physical agents being more efficient than biologically active ones 1,3,4,21 . Only Amit et al found that the use of an oxidized cellulose hemostatic agent resulted in longer time to drain removal, and consequently in length of hospital stay, if compared with conventional procedures, suggesting that postoperative hemorrhage can best be prevented by proper intraoperative hemostasis 25 .…”
mentioning
confidence: 78%
“…The use of hemostatic agents in thyroid surgery has been widely reported in the literature, but their effectiveness in preventing postoperative bleeding remains controversial 17 . Considering biologically active agents only, some studies demonstrated an advantage over standard treatment in terms of mean operation time, reduction of 24-h drain output, time to drain removal, incidence of post-operative seroma and length of hospital stay 1,3,4,[18][19][20][21][22] . Others found a lack of advantages on reducing perioperative bleeding, time to drain removal and length of hospital stay 23,24 , causing only additional costs 24 .…”
mentioning
confidence: 99%
“…The study suggested that fibrin-based hemostats should be used as a first-line hemostatic agent in thyroidectomy in combination with conventional surgical means of hemostasis [41].…”
Section: Intraoperative Considerationsmentioning
confidence: 99%
“…Studies for the biologically active agents demonstrate an advantage over standard treatment in the mean operation time, reduction of 24-h DV, time to drain removal, incidence of post-operative seroma and length of hospital stay [ 8 , 11 16 ]. However, not all studies confirm these findings [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%